2014
DOI: 10.1177/2045125314542098
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of the attitudes of patients in an early intervention service towards antipsychotic long-acting injections

Abstract: Objectives: The objective of this study was to investigate attitudinal themes to antipsychotic long-acting injections (LAIs) in patients in an early intervention team (EIT). Methods: Interviews were carried out with outpatients purposively sampled from an EIT to represent patients currently prescribed antipsychotic LAIs, oral antipsychotics and those not prescribed antipsychotic medication. Interviews were conducted and analysed according to grounded theory. Recruitment stopped when saturation of themes was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 26 publications
1
65
0
2
Order By: Relevance
“…In cases where LAIs are offered, patient tend to show a more favourable attitude of LAIs which correlate with their knowledge of these formulations (Potkin et al 2013). This is supported by systematic review of 12 studies by Waddell and Taylor (2009) and several other studies (Heres et al 2007, Patel et al 2009, Waddell and Taylor 2009, Caroli et al 2011, Das et al 2014). …”
Section: Patient's Views Of Laissupporting
confidence: 49%
See 1 more Smart Citation
“…In cases where LAIs are offered, patient tend to show a more favourable attitude of LAIs which correlate with their knowledge of these formulations (Potkin et al 2013). This is supported by systematic review of 12 studies by Waddell and Taylor (2009) and several other studies (Heres et al 2007, Patel et al 2009, Waddell and Taylor 2009, Caroli et al 2011, Das et al 2014). …”
Section: Patient's Views Of Laissupporting
confidence: 49%
“…Several studies have demonstrated that LAIs are welcomed by patients or even preferred (Walburn et al 2001, Phillips and McCann 2007, Iyer et al 2013, Das et al 2014) with at least one study suggesting an unfavourable view (Patel et al 2010). In situations where patients express an unfavourable view of LAIs, this may be because they have not been fully informed of LAIs as a treatment option.…”
Section: Patient's Views Of Laismentioning
confidence: 90%
“…128,129 In many cases, physician beliefs and perceptions about LAIs may prevent patients from learning that LAIs are a potential option. 130,131 For example, in a study of communication patterns in the offer of LAIs made by psychiatrists to patients with schizophrenia at 10 health clinics, psychiatrists generally presented LAIs in a negative light, resulting in only 11 of 33 LAI recommendations (33%) being accepted by patients. 132 However, during a postvisit interview, during which LAIs were presented in a more positive light and with more information, 27 of the 28 patients (96%) who declined the initial recommendation changed their mind, stating that they actually would be willing to try LAI treatment.…”
mentioning
confidence: 99%
“…In a survey of 317 psychiatrists, 69% regarded LAI-APs less acceptable to the patients, 48% as stigmatising, 40% as old fashioned and 38% more prone to adverse effects [17]. Patients may indeed associate LAIs with stigma and coercion [18]. Fear of needles and injection pain may also shape negative attitudes towards LAI-APs [19].…”
Section: Obstacles To Lais Usementioning
confidence: 99%